(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
Sara Saba, Isopoliteia in Hellenistic Times [Brill Studies in Greek and Roman Epigraphy], Leiden-Boston, Brill, 2020, p. 291. ISBN: 978-90-04-42569-9.